Wobbling and migrating ferrofluid droplets - Aaveg Aggarwal; Shih-Yuan Chen; Eleftherios Kirkinis; Mohammed Imran Khan; Bei Fan; Michelle M. Driscoll; Monica Olvera de la Cruz (Communications Physics)
Abstract Active components incorporated in materials generate motion by inducing conformational changes in response to external fields. Magnetic fields, in particular, carry the added advantage of biocompatibility as well as being able to actuate materials remotely. Although ferrofluid droplet migration induced by a high-frequency rotating magnetic field is a well-established effect, droplet migration at low frequencies is still elusive. Millimeter-sized ferrofluid droplets placed on a solid substrate, surrounded by an ambient gas phase, are shown here to migrate under a rotating magnetic field due to inertia-induced symmetry-breaking of the periodic deformation (wobbling) of the liquid-gas interface. This interface wobbling leads to droplet migration with speeds that increase as the amplitude and frequency of the magnetic field increase. In addition to migrating in a controlled manner, we demonstrate the ability of magnetic droplets to clean surface impurities and transport cargo.